The Improvement of Phonocardiograph Signal (PCG) Representation Through the Electronic Stethoscope - Sumarna Sumarna; Juli Astono; Agus Purwanto; Dyah Kurniawati Agustika (IAES Indonesia Section, 2017)
A conventional stethoscope (an acoustic stethoscope) is an acoustic medical device that is always used for preliminary examination of patients with any heart abnormalities. The main disadvantage of acoustic stethoscope is its dependence on how to use it and the experience of the examining physician. This paper presents a simple electronic stethoscope design in Phonocardiograph system that is free from subjectivity of doctors or other medical personnel. This electronic stethoscope is made sensitive in order to capture as many acoustic signal as possible from the activities of the human body, especially the heart and lungs. The design of this electronic stethoscope consists of chest piece, a pipe with proper acoustic impedance, mic condenser, mic preamp, and battery. The output of the mic preamp is connected to the mic channel on the laptop. The recording signal then processed separately. The repeatability of output signal was investigated in this paper. The signal was analyzed by using the Fast Fourier Transform (FFT). The result showed that the frequency responsea of the output signals are consistent, hence the instrument is reliable. Furthermore, the frequency response of the system with filter that connecting chest piece and mic condensor were also investigated.